IMPLEMENTASI SEMANGAT PERSATUAN PADA MASYARAKAT MULTIKULTURAL MELALUI AGENDA FORUM KERUKUNAN UMAT BERAGAMA (FKUB) KABUPATEN MALANG - Suryawan, Nashrul Wahyu; Danial, Endang (HUMANIKA, 2016)
The background of this research is the social diversity of Indonesian people. This situation causes conflicts among Indonesian people which need solutions to minimilize the effects of the conflict among the society. The study over the value of unification and harmony of the Religious Community Forum is one of the implementation of the unification spirit, the aspect of toleration, which needs to be spread out among the society. The goal of this research is to dig down how the Religious Community Forum works in increasing the Malang multicultural society understanding over the value of unification. It is also to know how the Religious Community Forum increases the society toleration and the importance of unification among Malang society diversity. Alt last but not least, the study over the unification value functions as a report of how the Religious Community Forum maintain the Indonesian people unification. This research use subjects of the Religious Community Forum members, religion leaders, government officers, and Malang people. The approach used in this research is qualitative with case study method. The data collection techniques used in this study are observation, interview, documentation, and participation. Meanwhile, the data is analyzed by using data reduction, data display, and verivication.The findings of this research are: 1) The activities done by the Religious Community Forum contain the unification value; the unification and harmony religious communities, conflicts and dialogues counseling, toleration, socialization over the government policy of the unification and harmony of diverse society; 2)The Religious Community Forum contains social aspects; the diversity value, toleration, pluralism, and the society unification, which can be descended to the next generation; 3) The forum has some roles in maintaining and keeping the unification value of multicultural society through the activities applied in the society. Malang government supports and coordinates any institution works in society unification and harmony. The actions taken shows that the government are concerned on the unification of multicultural society. Thus, it can be concluded that the activities done by the Religious Community Forum of Malang contain the unification value